2020
DOI: 10.3390/rs12182887
|View full text |Cite
|
Sign up to set email alerts
|

Albedo Impacts of Changing Agricultural Practices in the United States through Space-Borne Analysis

Abstract: Using the collocated Moderate Resolution Imaging Spectroradiometer (MODIS)-derived Bidirectional Reflectance Distribution Function (BRDF) with the U.S. Department of Agriculture’s National Agricultural Statistics Service’s Cropland Data Layer (CDL), the daily albedo of homogenous agricultural fields was derived for 51 common United States field crops by wavelength, sky-type, day of year, crop, and hardiness zone from 2015–2018. This study suggests that crop growth can result in changes in reflectivity up to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For example, through in situ measurements, Miller et al (2016) and Lei et al (2023Lei et al ( , 2024 observed comparable surface reflectance of 0.18-0.20 and 0.21-0.23 over a growing season at a sufficiently large corn field, which led to similar RF ∆α cooling of approximately −5.5 W m −2 when converted to a switchgrass landscape. Using Landsat and Sentinel satellite observations, Starr et al (2020), Carrer et al (2018), Shao et al (2014), and Bsaibes et al (2009) also observed similar surface reflectance over the study areas. However, as these orbiting satellites only provide a snapshot of local time at approximately 10:00-10:30 h, RF ∆α and GWI∆α based on satellite measurements are biased compared to those from the continuous in situ measurements (Cai et al 2016, Sieber et al 2019, Sciusco et al 2022.…”
Section: Limitations In Current Estimates Of Albedomentioning
confidence: 61%
“…For example, through in situ measurements, Miller et al (2016) and Lei et al (2023Lei et al ( , 2024 observed comparable surface reflectance of 0.18-0.20 and 0.21-0.23 over a growing season at a sufficiently large corn field, which led to similar RF ∆α cooling of approximately −5.5 W m −2 when converted to a switchgrass landscape. Using Landsat and Sentinel satellite observations, Starr et al (2020), Carrer et al (2018), Shao et al (2014), and Bsaibes et al (2009) also observed similar surface reflectance over the study areas. However, as these orbiting satellites only provide a snapshot of local time at approximately 10:00-10:30 h, RF ∆α and GWI∆α based on satellite measurements are biased compared to those from the continuous in situ measurements (Cai et al 2016, Sieber et al 2019, Sciusco et al 2022.…”
Section: Limitations In Current Estimates Of Albedomentioning
confidence: 61%
“…There is no network to provide this kind of data for agricultural crops especially in developing countries. Therefore, collecting experimental albedo data is crucial for model development and comparing model results (Starr et al, 2020). Having actual albedo values for plants is also useful in order to validate remote sensing data too (Dexter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in many applications, the albedo value is taken as a constant for a crop to represent the whole growing period, but it changes during the development period. However, as Dixon (1983) and Starr et al (2020) pointed out, albedo changes over time and many factors affect this change. So albedo is not constant.…”
Section: Introductionmentioning
confidence: 99%